The development of a composite sustainable development indicator for a corporate retail enterprise - Saul Rosenburg, Marshall Mabin, Neil Ackermann, Ernest Fortoh (Department of Environmental and Geographical Science, 2014)
Includes bibliographical references (leaves 134-145).